2022
DOI: 10.3390/ejihpe12120128
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Spirituality, Happiness, and Prosocial Bystander Behavior in Bullying—The Mediating Role of Altruism

Abstract: Positive psychology is vital in increasing prosocial behavior and reducing bullying. However, limited studies have analyzed the influence of positive personal characteristics on the prosocial behaviors of bystanders in bullying. The present study examined direct and indirect relationships between spirituality, happiness, altruism, and prosocial bystander behavior in bullying. Participants in this study were 685 students from Northwestern Mexico; 51% were male and 49% female, between 12 and 18 years old (M = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Consistent with these findings, Babanazari et al (2012) also reported that spiritual intelligence significantly predicts happiness. The results of another study conducted by García-Vázquez et al (2022) suggested that spirituality and happiness have an indirect relationship through the positive effects of altruism such that individuals with higher spirituality are more likely to engage in altruistic behaviors, which in turn results in an increase in the level of happiness. Spiritual beliefs also give hope to individuals and enable them to positively interpret the hurdles of life and also give them hope of having a peaceful everlasting life (Faribors et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, Babanazari et al (2012) also reported that spiritual intelligence significantly predicts happiness. The results of another study conducted by García-Vázquez et al (2022) suggested that spirituality and happiness have an indirect relationship through the positive effects of altruism such that individuals with higher spirituality are more likely to engage in altruistic behaviors, which in turn results in an increase in the level of happiness. Spiritual beliefs also give hope to individuals and enable them to positively interpret the hurdles of life and also give them hope of having a peaceful everlasting life (Faribors et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The interviews indicate that introducing spirituality into educational practises may be an effective technique for decreasing bullying and increasing an environment that is safe for learning and respecting others (Katarina Dutkova et al, 2017;Inez Garcia-Vazquez et al, 2022). Mindfulness exercises, storytelling sessions, and open talks about bullying are just some methods educators use to help students develop self-awareness, empathy, and moral standards (Bang & Lee, 2021;Battaglio, 2006;Buthelezi et al, 2021;Tekel & Karadag, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, the responses provide light on the transforming power of a spiritually-based educational setting (Inez Garcia-Vazquez et al, 2022). The research shows that this method can significantly affect pupils' attitudes, friendships, and success in life.…”
Section: Business Management and Strategymentioning
confidence: 95%
See 2 more Smart Citations